2009
DOI: 10.1088/1468-6996/10/1/014603
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous alignment and micropatterning of carbon nanotubes using modulated magnetic field

Abstract: We report simultaneous alignment and micropatterning of carbon nanotubes (CNTs) using a high magnetic field. It is important to prepare well-dispersed CNTs for alignment and patterning because CNT aggregation obstructs alignment. In magnetic field, highly anisotropic CNTs rotate in the direction stabilized in energy. Owing to their diamagnetic nature, CNTs suspended in a liquid medium are trapped in a weak magnetic field generated by a field modulator; meanwhile, they align to the applied strong magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…To effectively address these challenges, especially at a large-scale enabling mass-production level attractive for the industry and for real applications, there would evidently be less room for the conventional methods proposed earlier. These mainly include the simple wet mixing of CNT agglomerates and ceramic powders [18, 30, 37, 38]; beads milling using small 15–50 μ m beads [41]; jet milling using a diamond nozzle by high-pressure pump [39, 40]; in situ growth of ceramic clusters on poorly dispersed CNTs in a solution that necessarily has high ionic strength and poor colloidal stability [25]; solid-state, in situ , metal catalyst-assisted chemical vapor deposition (CVD) synthesis of low-quality, hydrophobic CNTs within a metal-ceramic powder framework [26]; and the conventional hetero-coagulation method [27]. In the wet methods, even if the CNTs are initially dispersed in a particular solvent through well-known surface functionalization routes followed by sonication [17, 51, 52], they would severely re-agglomerate upon solvent removal or the addition of ceramic-source precursor ions, reducing the zeta potential and colloidal stability.…”
Section: Scalable Processingmentioning
confidence: 99%
“…To effectively address these challenges, especially at a large-scale enabling mass-production level attractive for the industry and for real applications, there would evidently be less room for the conventional methods proposed earlier. These mainly include the simple wet mixing of CNT agglomerates and ceramic powders [18, 30, 37, 38]; beads milling using small 15–50 μ m beads [41]; jet milling using a diamond nozzle by high-pressure pump [39, 40]; in situ growth of ceramic clusters on poorly dispersed CNTs in a solution that necessarily has high ionic strength and poor colloidal stability [25]; solid-state, in situ , metal catalyst-assisted chemical vapor deposition (CVD) synthesis of low-quality, hydrophobic CNTs within a metal-ceramic powder framework [26]; and the conventional hetero-coagulation method [27]. In the wet methods, even if the CNTs are initially dispersed in a particular solvent through well-known surface functionalization routes followed by sonication [17, 51, 52], they would severely re-agglomerate upon solvent removal or the addition of ceramic-source precursor ions, reducing the zeta potential and colloidal stability.…”
Section: Scalable Processingmentioning
confidence: 99%
“…These results show that Nb 4 AlC 3 grain growth decreases the orientation degree. It is concluded that the susceptibility along the c ‐axis in the crystal structure of Nb 4 AlC 3 is higher than those along a ‐ and b ‐axes, which induces the rotation of Nb 4 AlC 3 particles with the c ‐axis parallel to the magnetic field direction in a strong magnetic field 14–21 . Probably, for all MAX phases, this phenomenon is similar owing to the similar electrical structures 40 …”
Section: Resultsmentioning
confidence: 97%
“…An assisting method seems to be necessary to obtain a preoriented MAX phase before sintering. In previous works, the control and design of the texture of Al 2 O 3 (hexagonal), AlN (hexagonal), Si 3 N 4 (hexagonal), and ZrO 2 (monoclinic), for example, have been successful in a high magnetic field 14–21 . The reason is that ceramic crystal with an asymmetric unit cell shows anisotropic susceptibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the Ti 3 SiC 2 grains could not be aligned to one direction, the ceramic texture was not homogeneous and the texture degree was low. Recently, tailored Al 2 O 3 , Si 3 N 4 , ZrO 2 and AlN ceramics have been successfully prepared using the strong magnetic field alignment (SMFA) method [13][14][15][16][17][18][19]. In this process, the ceramic crystals with asymmetric unit cell rotate to minimize the total energy in the magnetic field [20].…”
Section: Introductionmentioning
confidence: 99%